The Digital Resilience Strategies Of Night-Time Culinary SMES (Evidence From Bandung Indonesia) - Andry Mochamad Ramdan; M Fikri Maulana; Bila Shavitri Damayanti; Selfi Apriliani (CV Putra Publisher, 2026)
This study explores digital resilience strategies within the Micro, Small and Medium Enterprises (MSMEs) ecosystem in the Lengkong Culinary Night area, Bandung. The ‘night economy’ phenomenon is often confronted with structural vulnerabilities, ranging from weather volatility to hyper-competitive spatial competition. Using a qualitative approach with a participatory case study and netnography design, this study investigates how the integration of digital infrastructure transforms the adaptive capabilities of street vendors. The research findings indicate that the adoption of contactless payment technologies and logistics aggregator platforms functions not merely as a marketing tool, but has evolved into an essential coping mechanism when physical interactions are disrupted. Through the lens of Dynamic Capabilities Theory, MSMEs have proven capable of sensing algorithmic market trends in real time, executing innovations nimbly, and restructuring their business models into hybrid offline-to-online (O2O) models. Furthermore, area governance that prioritises a community-based approach and cross-departmental collaboration has helped to strengthen the physical ecosystem underpinning this virtual resilience. This study formulates the Grassroots Socio-Technical Resilience model, which demonstrates that institutional resilience in the digital age can be organically built by the informal sector through the fusion of sociological creativity and technological adaptation. Keywords: Digital Resilience, Dynamic Capabilities, Economy, Hybrid Ecosystem, Lengkong Culinary Nigh